2014
DOI: 10.14411/eje.2014.063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold acclimation, cooling rate and heat stress on cold tolerance of the potato tuber moth Phthorimaea operculella (Lepidoptera: Gelechiidae)

Abstract: Abstract. This study was carried out to investigate the effects of cold acclimation, cooling rate and heat stress on supercooling capacity and cold hardiness of the potato tuber moth (PTM), Phthorimaea operculella Zeller (Lepidoptera: Gelechiidae). Supercooling points (SCP) of first and last instar larvae, prepupae and pupae were -21.8, -16.9, -18.9 and -18.0°C, respectively. Cold acclimation (1-week at 0 and 5°C) did not affect SCPs of acclimated last instar larvae, prepupae and pupae. LT 50 s (lower lethal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
6
19
0
Order By: Relevance
“…According to the most recent classification of insects related to cold tolerance (Bale, 2002), P. operculella can be classified in the category of insects that are chill tolerant rather than freeze intolerant. In agreement with our observations, Hemmati et al (2014) also reported the incapability of a laboratory colony of P. operculella to tolerate subzero temperatures above their SCPs, though to a lesser extent. In agreement with our observations, Hemmati et al (2014) also reported the incapability of a laboratory colony of P. operculella to tolerate subzero temperatures above their SCPs, though to a lesser extent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the most recent classification of insects related to cold tolerance (Bale, 2002), P. operculella can be classified in the category of insects that are chill tolerant rather than freeze intolerant. In agreement with our observations, Hemmati et al (2014) also reported the incapability of a laboratory colony of P. operculella to tolerate subzero temperatures above their SCPs, though to a lesser extent. In agreement with our observations, Hemmati et al (2014) also reported the incapability of a laboratory colony of P. operculella to tolerate subzero temperatures above their SCPs, though to a lesser extent.…”
Section: Discussionsupporting
confidence: 93%
“…In most species supercooling capacity is regarded to be stage specific (Sømme, 1982;Lee, 1991). This is in agreement with previous reported studies where acclimation at 5 and 0°C for 1 week did not alter the supercooling capacity of P. operculella (Hemmati et al, 2014). Moreover, given that individuals originated from field-collected potatoes that were harvested in mid-September, when already minimum air temperatures in this area dropped below 10°C, both immature stages and adults may already have undergone cold acclimation in the field.…”
Section: Discussionsupporting
confidence: 90%
“…Followed by eggs the next development stage having a low SCP were first and second instars while later instar larvae, late pupae and adult had higher supercooling points. Among the larval stages of PTM, Hemmati et al (2014) found the lowest SCP value for the first instar, whereas it was highest in case of last instar larvae for an Iranian population, which is in line with our study. Park et al (2017) also found the lowest SCPs for the egg stage of Parnassius bremeri.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest supercooling point of eggs and early larvae may be due to their small sizes (Carillo & Cannon 2005;Hahn et al 2008;Zheng et al 2011;Hemmati et al 2014). Followed by eggs the next development stage having a low SCP were first and second instars while later instar larvae, late pupae and adult had higher supercooling points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation